(untitled) - Mundlak, Yair (Cambridge, MA, 2000)
This book covers aspects of the modern economics of agriculture and its place in the growing economy. It presents a theory of the growth of the agricultural sector within the context of a growing economy. The author explores the various aspects of the dynamics of agriculture and their relationship to the dynamics of the economy at large, offering a unique blend of theory, methodology, and empirical analysis
Keywords: Agriculture,Economic development.,Agriculture and state; Economic aspects; United States